THE RIGID-FLEXIBLE COUPLING VIBRATION CHARACTERISTICS ANALYSIS AND STRUCTURE IMPROVEMENT OF CENTRIFUGAL ELECTRIC SPINDLE - HE QingZhong; WANG YongBin; ZHAO XianDan; WANG YuHao (Jixie qiangdu)
Regarding the new type of centrifugal spinning electric spindle as the research object,the method of rigid-flexible coupling was used to build the dynamic model of electric spindle; On the basis of modern computer simulation technology,the system vibration characteristic analysis was finished by using the combining simulated technique of Adams and Ansys,get the forced vibration amplitude frequency,phase frequency characteristic,then the electric spindle structure was improved,and software verification on the improvement. Experimental results shows: the structure improvement practical and effective.